Um passeio por várias álgebras na descrição do momento angular - Belançon, Emerson Dionísio; Silva, Samuel Da (Sociedade Brasileira de Física, 2019)
Abstract The most common way to mathematically define the angular moment is through the vector product operation as defined by Josiah Willard Gibbs and at the same time by Oliver Heaviside. This way, the contribution of this article is to show that the definition of angular moment can also be made using other algebraic systems existing and less known to most students, such as Hamilton algebra, Grassmann algebra and Clifford geometric algebra. Finally, we make a critical comparison between these definitions and their meanings.

Resumo A forma mais comum de definir matematicamente o momento angular é através da operação de produto vetorial como definido por Josiah Willard Gibbs e ao mesmo tempo por Oliver Heaviside. Neste sentido, a contribuição deste artigo é mostrar que a definição do momento angular também pode ser feita usando outros sistemas algébricos existentes e menos conhecidos da maioria dos estudantes, como a álgebra de Hamilton, a álgebra de Grassmann e a álgebra geométrica de Clifford. Por fim, realizamos uma comparação crítica entre estas definições e o seus significados.
A walk through multiple algebras in the description of the moment angular
Keywords: angular moment; algebra; quaternion; vectors; multivectors; Hamilton; Grassmann; Clifford; momento angular; álgebra; quatérnion; vetores; multivetores; Hamilton; Grassmann; Clifford